Wilson?s disease presenting as rapid eye movement sleep behavior disorder: a possible window to early treatment - Gotthard G. Tribl; Edson Bor-Seng-Shu; Mateus C. Trindade; Leandro T. Lucato; Manoel J. Teixeira; Egberto R. Barbosa (Arquivos de Neuro-Psiquiatria)
Objective To describe characteristics of REM sleep behavior disorder in Wilson’s disease. Method Questionnaire-based interviews (patients and relatives), neurological examinations, two-week prospective dream-diary, video-polysomnography, transcranial sonography, MRI. Results Four Wilson’s disease cases with REM sleep behavior disorder were described; three had REM sleep behavior disorder as initial symptom. All showed mesencephalic tegmental/tectal sonographic hyperechogenicities and two presented ponto-mesencephalic tegmental MRI hyperintensities. Conclusion This first description of REM sleep behavior disorder in Wilson’s disease in literature documents REM sleep behavior disorder as a possible presenting symptom of Wilson’s disease and adds further evidence to the parallelism of Parkinson’s disease and Wilson’s disease in phenotype and brainstem topography, which ought to be further studied. REM sleep behavior disorder has prognostic relevance for neurodegeneration in α-synucleinopathies. In Wilson’s disease, usefulness of early diagnosis and treatment are already well established. REM sleep behavior disorder in Wilson’s disease offers a possible theoretical model for potential early treatment in this extrapyramidal and brainstem paradigm syndrome, previewing the possibility of neuroprotective treatment for REM sleep behavior disorder in “pre-clinical” Parkinson’s disease.